On the nature of a1 and a2 antigenic differences: the role of glycoprotein and glycolipid agglutinogenic glycotopes in their formation. - Delevsky Yu.P.; Dimitrova N.V.; Delevskaya V.Yu. (Крокус, 2003)
We used absorption of monoclonal reagents of Workshop IV (anti-A1 2-24, 2-25, 2-26, 2-27; anti-A 2-4, 2-10, 2-28; anti-H 2-71, 2-74) and anti-Ahp protectin by A1 and A2 erythrocytes, as well as inhibition of the above reagents and protectin by glycoconjugates received by enzymatic treatment of membranes, chloroform-methanol method and column anion-exchange chromatography. Unlike anti-A, anti-A1 reagents poorly reacted with glycolipid conjugates (Alp), were stronger inhibited by glycoprotein ones of the alkaline type (Apr-0, pH zone of 7,9-7,65) and significantly poorer reacted with the acidic type of glycoprotein conjugates (Apr-1, Apr-2, pH zone of 7,1-6,5). From A2 membranes, besides Alp, Apr-1 zone revealed glycoconjugates with H specificity, while in the acidic zone Apr-2 were found. The antigenic spectrum of A1 erythrocytes was represented more completely.